EFFECTS OF ANXIETY ON IN-CLASS SPEAKING PERFORMANCE AMONG ULIS FIRST-YEAR MAINSTREAM ENGLISH MAJORS - Nguyễn, Phương Thảo (2021)
As the study is finished, it is expected to be of great benefits for the target population, their teachers and other researchers interested in this topic. To begin with, the paper raises awareness of students and teachers of effects of anxiety on students‘ performance. Besides, the finding can help teachers to have alert choices for speaking activities to alleviate effects of anxiety. Last but not least, the paper can be the reliable reference for those who want to exploit more anxiety phenomenon